Strategi Manajemen Kelas Dengan Teknologi Digital - Linda Lestari; Gita Salamah Munthe; Dini Rahmayani; Muhammad Zulham Munthe (Jurnal Zeniusi, 2024)
This research aims to investigate the extent to which the implementation of digital technology and effective classroom administration enhances the quality of education at Madrasah Ibtidaiyah. Establishing a learning environment conducive to learning necessitates the implementation of rules and procedures, regulating student behavior, and the physical configuration of the classroom. Furthermore, digital technology is instrumental in facilitating the learning process, as it enables access to information and interactive learning through hardware such as computers and devices, as well as software and internet-based applications. This research indicates that integrating digital technology into classroom management can improve student engagement in learning, facilitate more active participation, and promote the development of 21st-century skills, including digital literacy, collaboration, and problem-solving. Digital technology enables the development of a dynamic and more effective learning environment by allowing learning to be more interactive, flexible, and customized to the unique requirements of each student. The significance of incorporating digital technology to develop learning pertinent to the requirements of technological advancement in the digital age is underscored by the implications of this research.